Ovarian fibrothecoma in an adolescent: A case report - Raphael H. Parrado; Macelyn Batten; Michael Smith; Lucas A. McDuffie (Elsevier, 2023)
Introduction: Ovarian fibrothecoma is a rare subtype of ovarian sex-chord stromal tumor canonically described in peri-menopausal and post-menopausal women. There have been some cases reported in young adults; however, there have not been any cases documented in the adolescent patient population. Case report: We present the youngest recorded case of an ovarian fibrothecoma. A 13 year old female presented with pelvic pain and non-specific symptoms. Diagnostic workup showed a mixed-density ovarian mass and tumor markers within normal limits. A right ovarian mass was resected without complication. The final pathology revealed a fibrothecoma. Conclusion: This case identifies a new type of ovarian mass that can present in adolescents and should be considered during the workup for adolescents with ovarian masses.